2019
DOI: 10.4103/jfmpc.jfmpc_315_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of periodontal status among nicotine dependent individuals of 35-44 years attending community dental camps in Ghaziabad district, Uttar Pradesh

Abstract: Background: Tobacco is the second driving reasons for mortality worldwide and its broad utilization in the smoking and smokeless form have added to the expanding weight of non-communicable disease. Aim: To study the prevalence of periodontal status among nicotine dependent individuals of 35-44 years attending community dental camps in Ghaziabad District, Uttar Pradesh. Methods: A cross-sectional study was conducted on 800 individuals with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…The group D (>60 years) showed the highest rate (82.6%) of periodontitis patients (Table V). Goyal et al;2019 found that localized chronic periodontitis was the most prevalent in the age group of 25-45 years (44.03%), while generalized chronic periodontitis was observed in the 46-65 age group (12.88%) [34]. In Hossain MZ et al [25] study, the prevalence and severity of gingivitis was found increased with age to a peak in the 21-30 years age group, whereas periodontitis increased significantly (p<0.001) in subjects above the age of 40 years in a population of Abha city of Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…The group D (>60 years) showed the highest rate (82.6%) of periodontitis patients (Table V). Goyal et al;2019 found that localized chronic periodontitis was the most prevalent in the age group of 25-45 years (44.03%), while generalized chronic periodontitis was observed in the 46-65 age group (12.88%) [34]. In Hossain MZ et al [25] study, the prevalence and severity of gingivitis was found increased with age to a peak in the 21-30 years age group, whereas periodontitis increased significantly (p<0.001) in subjects above the age of 40 years in a population of Abha city of Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that majority of the participants were highly dependent smokers(48.8%) which urged an attention to the necessities for building up a suitable instructive, preventive and treatment measure combined with successful reconnaissance for tobacco end among the population in Goyal et al, (2019).…”
Section: • Follow Up Visit (Contemplation Stage/preparation Stage )mentioning
confidence: 70%
“…Associations have been reported between cigarette smoking and root caries (Fure, 2004;Phelan, 2004), coronal caries (Axelsson et al, 1998) endodontic treatment (Krall, 2006), and periapical periodontitis; (Kirkevang and Wenzel, 2003), although not consistently (Bergstrom et al, 2004). A Cross-section study conducted in India among 800 males also stated that individuals with high nicotine dependency had a high prevalence of periodontitis (Goyal, 2019). In contrast with the above studies, the present study which analyzed the association between nicotine dependence and the number of tooth loss due to periodontal diseases had shown no statistical signi icance.…”
Section: Resultsmentioning
confidence: 99%